1992
DOI: 10.1002/ange.19921040944
|View full text |Cite
|
Sign up to set email alerts
|

Hydridübertragung durch Hydridokomplexe, ionische Hydrierung von Aldehyden und Ketonen sowie Struktur eines Alkoholkomplexes

Abstract: terschied zur planaren Konformation (7.4 kcalmol-') und die mit IGLOL' berechnete chemische Verschiebung fur C2 (169)[12] stimmen gut mit den fur 3a experimentell ermittelten Daten uberein. Abb. I . Schakalzeichnung der Molekulstruktur des Anions in 3a im Kristall. Wichtige Abstinde [pm] und Winkel ["I:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Stoichiometric ionic hydrogenations of ketones can be accomplished under mild conditions by addition of a strong acid (HOTf; OTf = OSO 2 CF 3 ) to solutions containing ketones and metal hydrides. [18] These reactions document that transition metal hydrides can function as hydride donors in the presence of a strong acid. As shown in generalized form in Eq.…”
Section: -H )]mentioning
confidence: 99%
“…Stoichiometric ionic hydrogenations of ketones can be accomplished under mild conditions by addition of a strong acid (HOTf; OTf = OSO 2 CF 3 ) to solutions containing ketones and metal hydrides. [18] These reactions document that transition metal hydrides can function as hydride donors in the presence of a strong acid. As shown in generalized form in Eq.…”
Section: -H )]mentioning
confidence: 99%
“…Recently, there has been a considerable interest in understanding the mechanisms of hydride transfer reactions for the C 5 H 5 M(CO) 3 H ͑where MϭCr, W, Mo͒ type of complexes. 1 Several derivatives of the C 5 H 5 M(CO) 3 H complexes have been studied and explored as catalysts for protonation of olefins, aldehydes, and ketones.…”
Section: Introductionmentioning
confidence: 99%
“…1 Several derivatives of the C 5 H 5 M(CO) 3 H complexes have been studied and explored as catalysts for protonation of olefins, aldehydes, and ketones. Bullock and Song have demonstrated that the rate of hydride transfer for some derivatives of C 5 H 5 M(CO) 3 H is highly dependent on steric factors, temperature, and the strength of the M-H bond. [2][3][4] The C 5 H 5 M(CO) 3 H complex can function as a hydride, proton, or hydrogen donor and its conjugate is quite reactive and can react with a wide variety of ligands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Distances r(HÁÁÁH) in [Å] can be obtained from Eq. (11) [12,27,[91][92][93][94][95] where m is the NMR frequency in MHz and DR 1 (min) = 1/T 1 (min)(add) -1/T 1 (min)(WH). rðH Á Á Á HÞ ¼ 5:817ðm Á DR1ðminÞÞ À1=6 ð11Þ…”
Section: Preparation Of Mer-w(co)(no)[ochme 2 ](Pme 3 ) 3 (7)mentioning
confidence: 99%